Preoperative anaemia and outcome after elective cardiac surgery: a Dutch national registry analysis. (April 2022) - Hazen, Yannick J.J.M.; Noordzij, Peter G.; Gerritse, Bastiaan M.; Scohy, Thierry V.; Houterman, Saskia; Bramer, Sander; Berendsen, Remco R.; Bouwman, R. Arthur; Eberl, Susanne; Haenen, Johannes S.E.; Hofland, Jan; Ter Horst, Maarten; et al.
Abstract: Background: Previous studies have shown that preoperative anaemia in patients undergoing cardiac surgery is associated with adverse outcomes. However, most of these studies were retrospective, had a relatively small sample size, and were from a single centre. The aim of this study was to analyse the relationship between the severity of preoperative anaemia and short- and long-term mortality and morbidity in a large multicentre national cohort of patients undergoing cardiac surgery. Methods: A nationwide, prospective, multicentre registry (Netherlands Heart Registration) of patients undergoing elective cardiac surgery between January 2013 and January 2019 was used for this observational study. Anaemia was defined according to the WHO criteria, and the main study endpoint was 120-day mortality. The association was investigated using multivariable logistic regression analysis. Results: In total, 35 484 patients were studied, of whom 6802 (19.2%) were anaemic. Preoperative anaemia was associated with an increased risk of 120-day mortality (adjusted odds ratio [aOR] 1.7; 95% confidence interval [CI]: 1.4–1.9; P <0.001). The risk of 120-day mortality increased with anaemia severity (mild anaemia aOR 1.6; 95% CI: 1.3–1.9; P <0.001; and moderate-to-severe anaemia aOR 1.8; 95% CI: 1.4–2.4; P <0.001). Preoperative anaemia was associated with red blood cell transfusion and postoperative morbidity, the causes of which included renal failure, pneumonia, and myocardial infarction. Conclusions: Preoperative anaemia was associated with mortality and morbidity after cardiac surgery. The risk of adverse outcomes increased with anaemia severity. Preoperative anaemia is a potential target for treatment to improve postoperative outcomes.